2006
DOI: 10.1002/hipo.20214
|View full text |Cite
|
Sign up to set email alerts
|

3-Nitropropionic acid toxicity in hippocampus: Protection throughN-methyl-D-aspartate receptor antagonism

Abstract: The over-activation of glutamate receptors can lead to excitotoxic cell death and is believed to be involved in the progression of neurodegenerative events in the vulnerable hippocampus. Here, we used an in vitro slice model to study toxicity produced in the hippocampus by the mitochondrial toxin 3-nitropropionic acid (3-NP). The organotypic slice cultures exhibit native cellular organization as well as dense arborization of neuronal processes and synaptic contacts. The hippocampal slices were exposed to 3-NP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 72 publications
1
25
0
2
Order By: Relevance
“…It has also been reported that systemic 3-NP administration produces oxidized proteins in the striatum and cortex as well as massive loss Fontaine 2000). Researchers also confirmed 3-NP-induced lesions and oxidative damage in hippocampus (Rodríguez-Martínez et al 2004;Silva et al 2007;Karanian et al 2006;Burda et al 2005). Turan and coworkers reported that chemical preconditioning with 3-NP reduces infarct size via a mechanism that may involve increased bioavailability of NO and decreased ONOOformation (Turan et al 2006).…”
Section: Discussionmentioning
confidence: 78%
“…It has also been reported that systemic 3-NP administration produces oxidized proteins in the striatum and cortex as well as massive loss Fontaine 2000). Researchers also confirmed 3-NP-induced lesions and oxidative damage in hippocampus (Rodríguez-Martínez et al 2004;Silva et al 2007;Karanian et al 2006;Burda et al 2005). Turan and coworkers reported that chemical preconditioning with 3-NP reduces infarct size via a mechanism that may involve increased bioavailability of NO and decreased ONOOformation (Turan et al 2006).…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, memantine was neuroprotective against rotenone, which an inhibitor of mitochondrial complex I (Rojas et al 2008) and reduced ROS and lipid peroxidation induced by organophosphate in rat brain (Zaja-Milatovic et al 2009). Memantine also prevent the deleterious effects of mitochondrial dysfunction induced by complex II inhibitors, malonate and 3-nitropropionic acid (Schulz et al 1996;Karanian et al 2006;Volbracht et al 2006). In brain tissue, it was showed that the complex I site can contribute up to 50% of total ROS generation (Kudin et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Schulz et al (1996), reported that memantine prevented the volumetric changes in the mouse striatum following administration of malonate, a complex II inhibitor, demonstrating that memantine could be used to prevent the deleterious effects of mitochondrial dysfunction. In vitro studies have shown that memantine diminishes the toxicity induced by 3-nitropropionic acid, another complex II inhibitor, in cerebellar granular cell cultures (Volbracht et al, 2006), cholinergic neurons (Wenk et al, 1996), and hippocampal slices (Karanian et al, 2006). Despite the evidence supporting a relevant role of complex I inhibition in neurodegeneration, the effects of memantine against complex I inhibition have remained largely unexplored.…”
Section: Discussionmentioning
confidence: 99%